The Coronavirus Disease 2019 Crisis as Catalyst for Telemedicine for Chronic Neurological Disorders - Bloem, Bastiaan R; Dorsey, E Ray; Okun, Michael S (Archives of neurology (Chicago), 2020)
This Viewpoint describes the reasons for and reality of a rapid advance towards telemedicine in neurology during the coronavirus disease 2019 pandemic.